2019
DOI: 10.1128/jcm.01254-19
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of “ Haemophilus quentini ” Strains Causing Invasive Disease in Ontario, Canada (2016 to 2018)

Abstract: Haemophilus influenzae is a well-established human pathogen capable of causing a range of respiratory and invasive diseases. Since the 1970s, it has been observed that a nontypeable cryptic genospecies of H. influenzae, most often biotype IV, has been associated with the genitourinary tracts of females and with invasive neonatal infections. This distinct genospecies has been provisionally named “Haemophilus quentini.” Here, we report seven cases of invasive H. quentini disease in patients from Ontario, Canada,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…H. quentini has also been isolated from urine and urethral cultures in adult males (224). Between 2016 and 2018, the Public Health Ontario laboratory in Toronto identified seven cases of invasive H. quentini infection (225). Two of the isolates were from neonates, three were from adult females of childbearing age (2 were known to be pregnant), and one was from an elderly female.…”
Section: Invasive Disease and Haemophilus Quentinimentioning
confidence: 99%
See 1 more Smart Citation
“…H. quentini has also been isolated from urine and urethral cultures in adult males (224). Between 2016 and 2018, the Public Health Ontario laboratory in Toronto identified seven cases of invasive H. quentini infection (225). Two of the isolates were from neonates, three were from adult females of childbearing age (2 were known to be pregnant), and one was from an elderly female.…”
Section: Invasive Disease and Haemophilus Quentinimentioning
confidence: 99%
“…H. quentini strains were identified as nontypeable, biotype IV, possessed sodC, and lacked fucK, with detection of the H. quentini-specific 16S rRNA gene and near-full-length 16S rRNA gene sequencing, tests which require referral to a reference laboratory. Given the need for testing not generally available in routine diagnostic laboratories, H. quentini may well be an underrecognized pathogen in adults, especially in pregnant women (225).…”
Section: Invasive Disease and Haemophilus Quentinimentioning
confidence: 99%
“…Martin and colleagues described a case of NTHi bacteremia due to acute endometritis, in which the uterus appeared to be the nidus of NTHi infection with no known primary focus [14]. Also, it has been reported that Haemophilus quentini, a NTHi biotype IV isolate, may have a predilection for female urogenital tract [15]. While identification of H. quentini isolates are not currently feasible at frontline laboratories, it is worth noting that NTHi could be an important causative pathogen of gynecological infections.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the genital specificity of serologically non-typable H. influenzae biotype IV were considered to represent a new Haemophilus species, named as ‘ Haemophilus quentini ’ [8, 9, 12, 13]. In this report, we describe a novel Haemophilus species isolated from human semen, which is phylogenetically related to H.…”
Section: Full-textmentioning
confidence: 99%